The Influence of Competence and Work Discipline on the Performance of Civil Servants in South Lampung - Sugiyanto, Hery; Wulansari, Wulansari (Universitas Sang Bumi Ruwa Jurai, 2024)
This study explores the effectiveness of good governance in enhancing the performance of civil servants in the context of Indonesia’s bureaucratic reform era. As principles such as transparency, accountability, participation, and rule of law are increasingly institutionalized within public administration, their influence on employee behavior and service outcomes becomes a critical area of inquiry. Employing a qualitative case study approach, data were gathered through in-depth interviews, observation, and document analysis within selected local government institutions. The findings reveal that good governance fosters a culture of professionalism, strengthens internal accountability, and improves the responsiveness of civil servants. However, challenges remain, including digital infrastructure limitations, inconsistent governance literacy, and resistance to change among senior staff. Leadership commitment and organizational support are key factors in ensuring the success of governance-based performance strategies. This study concludes that integrating good governance into daily bureaucratic processes not only enhances individual performance but also contributes to institutional transformation toward a more transparent and service-oriented public sector.